2022
DOI: 10.1007/s10664-022-10168-9
|View full text |Cite
|
Sign up to set email alerts
|

SSPCatcher: Learning to catch security patches

Abstract: Timely patching (i.e., the act of applying code changes to a program source code) is paramount to safeguard users and maintainers against dire consequences of malicious attacks. In practice, patching is prioritized following the nature of the code change that is committed in the code repository. When such a change is labeled as being security-relevant, i.e., as fixing a vulnerability, maintainers rapidly spread the change, and users are notified about the need to update to a new version of the library or of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Either incorrect commits or line changes were selected. Substantial work has been conducted for ML-based models to identify correct vulnerability patches [12], [72]. Semantic filters or heuristics for correct vulnerability fixing lines is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Either incorrect commits or line changes were selected. Substantial work has been conducted for ML-based models to identify correct vulnerability patches [12], [72]. Semantic filters or heuristics for correct vulnerability fixing lines is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It's crucial in software maintenance to ensure that patches not only resolve issues but also maintain the overall functionality and performance of the software. Vulnerability detection: The FixMe dataset can be applied in various software security tasks, including vulnerability detection [1,13,14,28,37], CWE type prediction [38], and vulnerability fix detection [39][40][41]. Labeling the new code fixed by the commits or code after can be considered benign sample and code before can be taken as vulnerable samples for vulnerability detection as binary classification.…”
Section: Applications Of Fixmementioning
confidence: 99%
“…For example, Mirhosseini et al [37] found that projects that use automated pull requests upgrade dependencies 1.6x often as projects that did not use any tools. Other studies propose methods for detecting or obtaining more information about vulnerabilities from different software artifacts, including commits [39]- [43], bug reports [29], [44], [45], and mailing lists [46], [47]. Unlike these studies, we do not aim to detect vulnerabilities but to determine which libraries are vulnerable based on a vulnerability report.…”
Section: Related Workmentioning
confidence: 99%